Design, Synthesis and In-Vitro Evaluation of Polymer-linked Prodrug of Methotrexate for the Targeted Delivery to the Colon - Singla, Nishu; Sharma, Rajiv; Bhardwaj, T.R. (Letters in Drug Design & Discovery, 2014)
The different substituted polyphosphazene-linked azo prodrug of Methotrexate (9-12) and chitosan-linked azo prodrug of methotrexate (13) were synthesized and characterized by modern analytical techniques such as IR, 1H NMR, 31P NMR and GPC. The in-vitro stability study showed that all polymeric drug conjugates are stable in upper GIT (pH = 1.2) and small intestine (pH = 7.4). In-vitro drug release showed that polyphosphazene-linked azo prodrug of methotrexate (12) has maximum release (88.4%) in the presence of rat cecal content compared to chitosan linked azo prodrug of methotrexate (13). Therefore, the synthesized polyphosphazene linked azo based drug conjugates of methotrexate (9-12) are the potential candidates for colon targeted drug delivery system with minimal undesirable side effects.
Keywords: Prodrug